2012
DOI: 10.1111/j.1471-6712.2012.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐sharing experiences of relatives of persons with severe mental illness – a phenomenographic study

Abstract: Relatives of those suffering from severe mental illness experience multiple challenges and a complex life situation. The aim of this study was to describe life-sharing experiences from the perspective of relatives of someone with severe mental illness. A qualitative, descriptive study was performed, and interviews were carried out with eighteen relatives of persons with severe mental illness. A phenomenographic analysis, according to the steps described by Dahlgren and Fallsberg, was used to describe the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 37 publications
1
46
0
3
Order By: Relevance
“…Weimand et al. reported that relatives of people with severe mental illness found themselves wiser and more generous towards people's differences because of the illness and that it felt meaningful to help the mentally ill next of kin and others. In this study, the relatives described that they felt gratitude to their next of kin, and it was a matter of course to help.…”
Section: Discussionmentioning
confidence: 99%
“…Weimand et al. reported that relatives of people with severe mental illness found themselves wiser and more generous towards people's differences because of the illness and that it felt meaningful to help the mentally ill next of kin and others. In this study, the relatives described that they felt gratitude to their next of kin, and it was a matter of course to help.…”
Section: Discussionmentioning
confidence: 99%
“…Relatives of people with a mental illness are often oscillating between several emotions as they try to make meaning of their loved one's illness. According to Weimand, Hall‐Lord, Sällström, and Hedelin (), these emotions can develop across a spectrum of feelings that may strengthen or hinder relationships. Feelings of anger, disappointment, anxiety, and grief are not uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…They often play an important role as informal caregivers contributing to improvement of the patient’s health [15]. Furthermore, they are co-sufferers having been deeply involved in their family member’s suffering for years, and may themselves carry symptoms and ailments as a result of what they have been going through [68]. …”
Section: Introductionmentioning
confidence: 99%
“…Over the last 25 years, several policy initiatives have been taken to increase the involvement of NOK of people with serious mental health problems [13–15]. However, various barriers exist which limit necessary involvement of NOK [7, 8, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%